Entrepreneurial Education in the Context of the Imperative Development of Sustainable Business - Rădulescu, Carmen Valentina; Burlacu, Sorin; Bodislav, Dumitru Alexandru; Bran, Florina (European Journal of Sustainable Development, 2020)
Entrepreneurial education is one of the fastest growing areas in the world today, with a growing interest in academia, which allows the possibility of linking current labor market needs to academic theory. The purpose of this article is to make a positive contribution to the formation of future entrepreneurship programs, by analyzing existing curricula to identify potential educational gaps, as well as to identify the skills needed by students in the context of sustainable business development. This will allow entrepreneurial trainers to exchange ideas that facilitate collective learning and help inform researchers about the future directions of education. This article will focus on the analysis of existing entrepreneurship education at the international level, as well as on the development of suggestions on how entrepreneurship education can progress further, as a way of shaping the future development of the economy. Keywords: entrepreneurial education, sustainable business, sustainable development